(untitled) (Western European Journal of Medicine and Medical Science, 2025)
We examined 14 patients (including 5 women and 9 men). The average age of the patients was 30.6±9.3 years. All patients had nodular adrenal hyperplasia detected on MRI. Twelve patients (85.7%) sought medical attention for arterial hypertension (AH), while two patients (14.3%) had no complaints. The patients were diagnosed with stage I obesity, with the average BMI in men Introdactionbeing 32.7±4.54 kg/m2, and in women - 31.1±3.78 kg/m2, with an abdominal distribution of subcutaneous fat. Arterial hypertension is the main symptom of adrenal masses. Arterial hypertension in men with incidentalomas is more malignant compared to women, which is confirmed by the detection of stage III hypertension in 22% of the examined men.